Methodology for assigning credit ratings to sovereigns - Philippe Muller; Jérôme Bourque (Bank of Canada, 2017)
The investment of foreign exchange reserves or other asset portfolios requires an assessment of the credit quality of investment counterparties. Traditionally, foreign exchange reserve and asset managers have relied on credit rating agencies (CRAs) as the main source for credit assessments. The Financial Stability Board issued principles to reduce reliance on CRA ratings in standards, laws and regulations, in support of financial stability. Moreover, best practices in the asset management industry suggest that investors should understand the credit risks they are exposed to and, more broadly, that internal credit assessments be relied upon to inform investment decisions. In support of efforts by market participants to establish stronger internal credit assessment practices, as well as to solicit feedback, this paper provides a detailed technical description of the methodology developed to assign internal credit ratings to sovereigns, using publicly available data only. This methodology proposes three key innovations: (i) a quantitative approach to assess political risks, (ii) a framework to assess the government's potential contingent liabilities related to the banking sector, and (iii) a framework to determine the presence of asset price imbalances in the country. The methodology presented relies on fundamental credit analysis that produces a forward-looking and "through-the-cycle" assessment of the investment entity's capacity and willingness to pay its financial obligations, resulting in an opinion on the relative credit standing or likelihood of default. The methodology presented is currently used to assess eligibility and inform investment decisions in the management of Canada's foreign exchange reserves. The methodology is a key component of the joint Bank of Canada and Department of Finance Canada initiative to develop internal credit assessment capabilities.
Keywords: G24; G28; G32; F31; 330; Credit risk management; Foreign reserves management